2010
DOI: 10.1212/wnl.0b013e3181f9626a
|View full text |Cite
|
Sign up to set email alerts
|

Dilation by CGRP of middle meningeal artery and reversal by sumatriptan in normal volunteers

Abstract: This study provides Class I evidence that IV GCRP causes dilation of the MMA but not the MCA in healthy volunteers, and that sumatriptan reverses the dilation of the MMA caused by CGRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
132
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(147 citation statements)
references
References 31 publications
9
132
1
2
Order By: Relevance
“…Using high-resolution magnetic resonance angiography (MRA) in a study of migraine without aura patients (8), we recently showed that sumatriptan constricted the middle meningeal artery (MMA), but not the middle cerebral artery (MCA), during migraine attacks. In contrast, we have previously reported that sumatriptan constricted both the MMA and the MCA in healthy volunteers (9), but suggested that it mainly constricted the MMA. To further explore a possible differential effect of sumatriptan on extracerebral versus cerebral arteries, we examined the effect of sumatriptan on the following additional arteries: the superficial temporal artery (STA), the extracranial part of the internal carotid artery (ICA extra ), the basilar artery (BA) and the intracranial part of the internal carotid artery (ICA intra ).…”
Section: Introductioncontrasting
confidence: 70%
“…Using high-resolution magnetic resonance angiography (MRA) in a study of migraine without aura patients (8), we recently showed that sumatriptan constricted the middle meningeal artery (MMA), but not the middle cerebral artery (MCA), during migraine attacks. In contrast, we have previously reported that sumatriptan constricted both the MMA and the MCA in healthy volunteers (9), but suggested that it mainly constricted the MMA. To further explore a possible differential effect of sumatriptan on extracerebral versus cerebral arteries, we examined the effect of sumatriptan on the following additional arteries: the superficial temporal artery (STA), the extracranial part of the internal carotid artery (ICA extra ), the basilar artery (BA) and the intracranial part of the internal carotid artery (ICA intra ).…”
Section: Introductioncontrasting
confidence: 70%
“…Finally, from a pathophysiological standpoint it has to be considered that evidence suggests that CGRP does not cross the BBB as its infusion induces a dilatation of the MMA but not of the MCA (104). Therefore, if the BBB remains intact, which might be questioned in spontaneous migraine attacks, can it be evaluated in the experimental setting?…”
Section: Pitfalls Of Measuring Neuropeptide Changesmentioning
confidence: 99%
“…1,3,12,14 Because the signal intensity of arteries on MR angiograms obtained by using the TOF method depends on the flow velocities and flow directions, measurement of an MMA diameter on MR angiograms could not reflect the exact diameter of the MMA.…”
Section: Limitationsmentioning
confidence: 99%
“…6,7 Quantitative measurement of MMA diameter with MRA in patients with migraine has also been reported. 1,3,12,14 To the best of our knowledge, no previous study has elucidated alteration of the MMA in patients with CSDHs. Clarification of MMA changes associated with the development of a CSDH may lead to elucidation of the pathogenesis of CSDH and may also ameliorate treatment strategies for refractory CSDH.…”
mentioning
confidence: 99%